Association between work–family conflict and overall well‐being among Chinese nurse leaders. (17th August 2020) - Yu, Junye; Song, Huanhuan; Shi, Haina; Wang, Keyi
Abstract: Aim: To explore the association between work–family conflict and overall well‐being among Chinese nurse leaders. Background: Nurse leaders are constantly busy at the clinical frontline, mostly experience high stress levels at work and have little time to spend with the family. There is little evidence to know about the association between work‐family conflict and overall well‐being, which is essential for high‐quality medical care. Methods: A cluster sampling method was used to recruit 42 nurse leaders. Data were collected using the Chinese versions of the Multidimensional Work–Family Conflict Scale and the General Well‐Being Schedule. Descriptive analyses, independent t tests, ANOVAs and Pearson's correlation were used for the statistical analysis. Results: The mean scores ( SD ) of work–family conflict and well‐being were 2.17 (0.57) and 4.51 (0.61), respectively. Negative correlations were observed with strain‐based and behaviour‐based work–family conflict and overall well‐being. Conclusion: Stress from work–family conflict is positively correlated with the overall well‐being of Chinese nurse leaders. Implications for Nursing Management: Hospital administrators should be aware of specific risk factors and implement accordingly the interventional strategies to decrease the stress levels and improve the overall well‐being of nurse leaders.